Financing of dental services in Turkey: Opinions and expectations of dentists, residents, and patients - MUMCU, GONCA (WILEY, 2004)
Objectives: This study investigates the attitudes of dentists, residents, and patients on the financing of dental services in Turkey. Methods: In this descriptive study, randomly selected groups of 860 dentists, 641 patients, and 866 residents from 9 provinces of Turkey were interviewed. Their agreement on various statements on financing issues of dental services were recorded and analyzed. Results: Eighty-two percent of the dentists, 83.8 percent of the patients, and 76.4 percent of the residents agreed that governments should finance all dental services. The majority of the dentists (83.6%), patients (74.7%), and residents (84.4%) stated that patients should pay a copayment for their dental treatment. Conclusion: Survey results indicate that the current financing system of dental services in Turkey is not satisfactory either for the providers or for the users.
Keywords: dental care; dental insurance; national health programs; OLDER